2016
DOI: 10.17795/jjhs-36555
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Identification of Cow’s Milk in Buffalo’s Milk and It’s Products Using the Polymerase Chain Reaction

Abstract: Background: In the dairy industry, protection against species substitution or admixture is important for several reasons, including frequent human adverse reactions toward some species milk proteins, and trade and government regulations. Objectives: The objective of the present study was to assess the purity of buffalo milk and it's products offered as "pure buffalo" in the market. Methods: Using species-specific primers, a duplex polymerase chain reaction (PCR) assay was performed to detect the fraudulent add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…The study shows that also fermented milk products are targets for food fraud and adulterations, confirming that milk and milk-based products are among the main targets of fraud, specifically concerning the widespread and frequent use of milk from different species in buffalo milk products, often even violating the provisions of the product specifications (Bottero et al, 2002;Di Pinto et al, 2004;Mafra et al, 2007;Czerwenka et al, 2010;Di Domenico et al, 2017;EFSA, 2019). Given the limited availability of statistics on the incidence of animal-based food product fraud in the European Union and the comparative lack of data about the presence of undeclared milk species in buffalo yogurt, this study-to our knowledge, the first report of cow milk undeclared in Italian buffalo yogurt-was in accordance with observations by Zarei et al (2016a), who found undeclared cow milk in 64% of Iranian yogurt labeled as pure buffalo milk. The results of this study were also in agreement with further findings of Zarei et al (2016b), that only 27.5% of the yogurt samples declared as being made from pure sheep milk proved to be so, whereas significant quantities of cow and goat milk were detected in 37.5 and 22.5% of those samples.…”
Section: Short Communicationsupporting
confidence: 89%
See 1 more Smart Citation
“…The study shows that also fermented milk products are targets for food fraud and adulterations, confirming that milk and milk-based products are among the main targets of fraud, specifically concerning the widespread and frequent use of milk from different species in buffalo milk products, often even violating the provisions of the product specifications (Bottero et al, 2002;Di Pinto et al, 2004;Mafra et al, 2007;Czerwenka et al, 2010;Di Domenico et al, 2017;EFSA, 2019). Given the limited availability of statistics on the incidence of animal-based food product fraud in the European Union and the comparative lack of data about the presence of undeclared milk species in buffalo yogurt, this study-to our knowledge, the first report of cow milk undeclared in Italian buffalo yogurt-was in accordance with observations by Zarei et al (2016a), who found undeclared cow milk in 64% of Iranian yogurt labeled as pure buffalo milk. The results of this study were also in agreement with further findings of Zarei et al (2016b), that only 27.5% of the yogurt samples declared as being made from pure sheep milk proved to be so, whereas significant quantities of cow and goat milk were detected in 37.5 and 22.5% of those samples.…”
Section: Short Communicationsupporting
confidence: 89%
“…Indeed, fraudulent incorporation of less expensive bovine milk into buffalo dairy products is common practice and has been widely reported throughout the world (Di Pinto et al, 2019). However, very few data are available about food fraud concerning fermented milk products and the presence of undeclared milk species in buffalo yogurt, a high-priced niche product around the world (Zarei et al, 2016a) with an array of health benefits, includ-ing improved intestinal and immune health (González et al, 2019;Savaiano and Hutkins, 2020). Considering the economic relevance of-and increased demand for-buffalo milk products, the aim of this study was to investigate the undeclared presence of cow (bovine) milk in yogurt declared as being made exclusively from water buffalo milk.…”
Section: Short Communicationmentioning
confidence: 99%
“…[ 18 ] and Zarei et al . [ 20 ]; they indicated that the percentage of adulterated samples was 50% and 70%, respectively. The high incidence of adulteration in this study in comparison with the previous studies due to the difference between the locations of the studies, in addition, the low numbers of buffalos and the low buffalo’s milk production in Assiut in compare with Mansoura, Egypt, and Iran.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-based methods to analyze milk authenticity are particularly focused on the analysis of mitochondrial DNA sequences, because its sequence is highly conservative within different animal species and gives high copy number in animal cells, increasing the specificity of the method (Zarei et al 2016). The selective amplification of the conserved region of mitochondrial cytochrome b gene specific to mammals was used for species identification (Bos, Ovis, Capra, Bubalus etc) in dairy products by PCR or PCR-RFLP.…”
Section: Milk Authenticationmentioning
confidence: 99%